2018
DOI: 10.12737/article_5b9858ead1b5e3.93619630
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Interleukin-6 Signaling in Development of Systemic Inflammation in Chronic Obstructive Pulmonary Disease

Abstract: The review focuses on the role of interleukin-6 (IL-6) signaling in the development of a systemic inflammatory process in chronic obstructive pulmonary disease (COPD). In most researches the attention is paid to local inflammation in COPD. However, it is known that the pathology is characterized by a systemic inflammatory process, which is manifested in the increased levels of proinflammatory mediators in blood flow, and the study of the molecular mechanisms of its development is very important for the therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
0
3
0
6
Order By: Relevance
“…According to modern studies, the implementation of IL-6 properties depends on the type of cell signaling [9]. The IL-6 receptor complex consists of IL-6R subunit, which is responsible for cytokine binding, and gp130 subunit, which provides JAK / STAT (janus kinase / signal transducer and activator of transcription protein) or MAPK (mitogen-activated protein kinase) signaling cascades.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to modern studies, the implementation of IL-6 properties depends on the type of cell signaling [9]. The IL-6 receptor complex consists of IL-6R subunit, which is responsible for cytokine binding, and gp130 subunit, which provides JAK / STAT (janus kinase / signal transducer and activator of transcription protein) or MAPK (mitogen-activated protein kinase) signaling cascades.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found an increase in sIL-6R levels in the blood and sputum of COPD patients [18] that indicates its important pathological role in this disease. It has reported that IL-6 provides for the recruitment of innate immunity cells in inflammatory focus in COPD by activating chemokine synthesis in endothelial cells via trans-signaling [9]. Le et.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Повышенная концентрация IL-6 у больных ХОБЛ имеет тенденцию к неуклонному росту по мере прогрессирования ХОБЛ. Именно поэтому IL-6 является маркером системного воспаления [30,31]. Поскольку IL-6 является цитокином, обладающим, помимо про-, еще и противовоспалительными свойствами, его молекулярная активность достигается путем взаимодействия со специальным рецепторным комплексом, состоящим из двух субъединиц: IL-6R и gp130.…”
Section: роль Il-6 в развитии воспаления при хобл и ожиренииunclassified
“…Результат реакции IL-6 с эф-фекторной клеткой напрямую зависит от типа сигналинга. В настоящее время известно три механизма передачи сигнала в клетку мишень: классический, кластерный и транссигналинг [29][30][31][32][33].…”
Section: роль Il-6 в развитии воспаления при хобл и ожиренииunclassified